تصميم برنامج الأنشطة التفاعلية على شبكة الأنترنيت في تعليم المتلازمات اللفظية وتقويم قابلية استخدامها - Amani Nawi (Universiti Sains Islam Malaysia, 2024)
The main objective of this study is to develop Web-based Interactive Activities for learning Arabic collocation (arabCollotivities) and to evaluate this learning activities from a usability perspective. This web-based interactive activity aims to provide Arabic second language students in higher learning institutions a platform for learning collocation and to assist them in learning this topic independently and in a fun way. The theoretical foundation of the study was profoundly based on the theory of Lexical Theory proposed by Lewis, Theory of Multimedia Learning by Mayer, Theory of Learning Events of Gagne and the ASSURE instructional design models provided by Smaldino, Lowther & Russell. This study employed the Design and Developmental Research Approach introduced by Ritchey and Klien. Based on this approach, the study was divided into three phases. The first phase involves the survey of needs analysis conducted on 150 students who are involve in Arabic language courses as compulsory subjects at the Tamhidi Center, Universiti Sains Islam Malaysia to see the needs of development these activities in their process of learning Arabic. The data was by descriptive statistics using the software Statistical Package for the Social Science (SPSS) version 21.0 to find the mean value and standard deviation. In the second phase, Fuzzy Delphi Method (FDM) technique was exploited which involves 12 panel of experts. This technique was used to design and to determine the essential elements and requirements that should be included in the development of collocation activities based on expert’s opinions and decisions. The third phase was the usability evaluation of prototype activities involving 60 students of Shariah and Law students studying Arabic as the second language at Tamhidi Center, Universiti Sains Islam Malaysia using Modified Nominal Group Technique (Modified NGT). The selection of these students is because they were the target group who will use this activity indirectly in their process of learning Arabic. The overall findings from the first phase showed that the students state that there were no exercises and activities related to collocation conducted in the classroom and materials or resources focusing on the learning of Arabic collocation are also very limited. The findings also found that students agreed that they lacked knowledge about collocation in Arabic even though, they realized the importance of this phenomenon. Therefore, study of the development of this web-based activity is required. Findings from the second phase generated the 5 main components and elemets contained therein. The main components included the objectives, content, teaching aids, strategies of information delivery and learning evaluation. Further, the findings from the third phase showed that all major areas of product usability were achieved, and the activity can be implemented after some of modification since the score percentage value of above 70% was accomplished.